2015
DOI: 10.1363/4108915
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Relationships Between Parental Monitoring, Peer Risk Involvement and Sexual Risk Behavior Among Bahamian Mid-Adolescents

Abstract: CONTEXT Considerable research has examined reciprocal relationships between parenting, peers and adolescent problem behavior; however, such studies have largely considered the influence of peers and parents separately. It is important to examine simultaneously the relationships between parental monitoring, peer risk involvement and adolescent sexual risk behavior, and whether increases in peer risk involvement and changes in parental monitoring longitudinally predict adolescent sexual risk behavior. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 35 publications
1
26
1
7
Order By: Relevance
“…Parental monitoring usually describes parental knowledge of the child's whereabouts, activities and company (Sieverding, Adler, Witt, & Ellen, 2005;Wang, Stanton, Deveaux, & Lunn, 2015), with the literature pointing to its importance for health sexual development 5 (Borawski, Ievers-Landis, Lovegreen, & Trapl, 2003). Wight, Williamson, and Henderson (2006) observed that young people with high parental monitoring at baseline reported fewer sexual experiences than their peers two years later.…”
Section: Buffering Role Of Parental Involvement?mentioning
confidence: 99%
See 1 more Smart Citation
“…Parental monitoring usually describes parental knowledge of the child's whereabouts, activities and company (Sieverding, Adler, Witt, & Ellen, 2005;Wang, Stanton, Deveaux, & Lunn, 2015), with the literature pointing to its importance for health sexual development 5 (Borawski, Ievers-Landis, Lovegreen, & Trapl, 2003). Wight, Williamson, and Henderson (2006) observed that young people with high parental monitoring at baseline reported fewer sexual experiences than their peers two years later.…”
Section: Buffering Role Of Parental Involvement?mentioning
confidence: 99%
“…Among female participants, high parental monitoring was also related to more frequent condom and contraception use. In a longitudinal study carried out among 13-to 17-year-old adolescents in the Bahamas, initial levels of parental control had protective effects on sexual risk-taking 18 months later among both male and female adolescents (Wang et al, 2015). Parental monitoring can also buffer the effects of adolescent exposure to problematic media content, either directly, by restring access, or indirectly--by enabling an active and mediating parental engagement.…”
Section: Buffering Role Of Parental Involvement?mentioning
confidence: 99%
“…This was congruent with studies conducted in Ethiopia (Negeri, 2014;Mariam et al, 2018;Mullu et al, 2016;Ali, 2017). However, it contradicts studies conducted in three Asian countries (Hanoi, Shanghai, and Taipei), Nigeria, Bahamas, Cambodia and else were in Ethiopia (Nigatu et al, 2018; Dadi and Teklu, 2014; Kahsay et al, 2017;Ifeadike et al, 2018;Wang et al, 2015). Maternal educational status was not a significant contributing factor to student"s risky sexual behaviors.…”
Section: Discussionmentioning
confidence: 80%
“…However, males in mid- and late- adolescence had lesser odds of transitioning to first sexual intercourse compared to those in early adolescence. Previous studies have shown that adolescents’ behavior is significantly correlated with that of their peers [ 13 , 43 ]. Thus, it is possible that male adolescents who resist peer pressure to engage in sexual intercourse in early adolescence may continue to resist pressure to become sexually active as they grow older.…”
Section: Discussionmentioning
confidence: 99%